Kapitał intelektualny i innowacyjność w kontekście rozwoju regionalnego - Richert-Kaźmierska, Anita (Intellectual Capital and Innovativeness in Regional Development Context, 2006)
Subject of the article is intellectual capital and innovativeness in regional development context. Intellectual capital is defined as input necessary to stimulate regional development and innovativeness as it's methodology and upper value. Author addressed issues of Polish regions low-level innovativeness and chances for their innovative potential growth thanks to creating Regional Innovation Systems and implementing Regional Innovation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 570-577